PENGARUH JENIS PELARUT PADA EKSTRAKSI MENGGUNAKAN GELOMBANG ULTRASONIK TERHADAP AKTIVITAS ANTIOKSIDAN EKSTRAK KULIT BUAH LEMON (Citrus limon (Linn.) Burm F.) - Verdiana, Melia; Widarta, I Wayan Rai; Permana, I Dewa Gede Mayun (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 7 No 4 (2018): Jurnal ITEPADO - 10.24843/itepa.2018.v07.i04.p08, 2018)
This study aims to determine the effect of solvent types on antioxidant activity of lemon peel (Citrus limon (Linn.) Burm F.) extract and to obtain the right solvent types with the highest antioxidant activity of lemon peel extract. The experimental design used in this research  was a completely randomized design with the treatment of solvent types (aquades, acetone 70%, ethanol 70% and methanol 70%). The treatment  was repeated four times to obtain 16 units of the experiment. Data were analyzed with analysis of variance (ANOVA) and followed by Duncan test. The result showed that the best treatment was obtained extract with ethanol 70% solvent with antioxidant activity was 52.72% and the IC50  value 471.33 mg/L, followed by yield was 37.68%, vitamin C was 227.90 mg AAE/g extract and total flavonoid was 7.14 mg QE/g extract.